Two Cases of Transverse Testicular Ectopia in Consanguineous Boys - Mohamed Abdelmalak; Saber Waheeb; Ahmed Koraitim; Dina Mahdy; Deena Mustafa Abd ElMigeid (Georg Thieme Verlag KG, 2018)
Abstract Crossed testicular ectopia (CTE)/transverse testicular ectopia (TTE) is a rare condition occurring in only 1 in 4 million male patients, in which both testes migrate toward the same hemiscrotum. We report on two cases of TTE in first degree cousins (1 + 3 years of age). Both presented with right nonpalpable testis. On diffusion-weighted magnetic resonance imaging, the right testis was located above the left testis in both patients. Right orchiopexy was performed after passing the right testis through the median raphe of the scrotum followed by ipsilateral left scrotal orchiopexy.